Long-Run Relationship Between Fiscal Policy and Economic Growth in Asia: Evidence Using Pedroni’s Cointegration Approach - Hussin Abdullah; Muzafar Shah Habibullah; Ahmad Zubaidi Baharumshah; Tan Boon Hui (Malaysian Management Journal, 2020)
This paper investigates the long-run relationship between fiscal policy and economic growth in Asia between 1982 and 2001 through the application of Pedroni’s Cointegration approach. It examines two different channels through which fiscal policy can affect long-run economic growth in Asian countries. The first channel is when components and aggregate government expenditure affect the real per capita GDP, and the second channel is when the distortionary taxation, budget balance, and aggregate of other fiscal variables affect the real per capita GDP. There is a positive and statistically significant impact of health and education expenditure, aggregate of government expenditure, and aggregate of other fiscal variables on real per capita GDP. It was found that the defence expenditure, distortionary taxation, and budget balance are significantly and negatively related to real per capita GDP. The Pedroni Cointegration result establishes a long-run relationship between fiscal policy and economic growth.